BRANDING DALAM ADMINISTRASI PENDIDIKAN: MEMBANGUN IDENTITAS DAN DAYA SAING LEMBAGA PENDIDIKAN MELALUI MANAJEMEN ADMINISTRASI YANG TERINTEGRASI - Aslan Aslan (ADMIN: Jurnal Administrasi Negara, 2026)
This article discusses branding in educational administration as a strategy for building the identity and competitiveness of educational institutions through integrated administrative management. This study employs a literature review method by examining various relevant sources related to the concepts of branding, educational administration, and integrated management. The findings indicate that branding in education is not limited to visual symbols but also encompasses service quality, consistency in institutional identity, administrative transparency, and positive user experiences. Integrated administrative management plays a crucial role in delivering efficient, accurate, and responsive services while supporting data-driven decision-making. Integration between academic, financial, human resources, and general service aspects strengthens the institution’s image while enhancing public trust. Thus, branding through integrated administration becomes a vital strategy in reinforcing the existence and competitive advantage of educational institutions in the modern era.